Sujeitos em trânsito: figurações do espaço urbano em O sol na cabeça, de Geovani Martins - Evandro Batista Siqueira (2021)
This dissertation proposes to investigate the representation of Carioca's Urban Space, through the look and the walk of peripheral characters passing by alleys, streets, and beaches from Rio de Janeiro, in "O sol na cabeça" (2018), short-tales book in which Geovani Martins makes his literary debut. The discussions exposed here are centered, on one side, to analyses the relation between the individual and the collectivity that emanating from reflections about the situations lived by the protagonists of the short-tales in these spaces, and, on the other hand, focus on the aesthetical and the social nature that fit the author and his characters investigating the relation between literature and marginality. Therefore, is used a transdisciplinary theoretical base that throughout many different fields of knowledge as Humanist Geography, Philosophy, Anthropology, and Literary Theory. These studies helped to reflect about urbanization, globalization, and cultural studies. Such analysis uses mobility as the reading operation of Martins' work to explore the several ways of the characters in their displacement through the narrative space and the meanings referring to the territorial identity from the historical, cultural, and affective point of view in the relations of the characters with the urban space in the everyday life.